Hippocampal-anterior thalamic pathways for memory: uncovering a network of direct and indirect actions. - O'MARA, SHANE (My University, 2010)
This review charts recent advances from a variety of disciplines that create a new perspective on why the multiple hippocampal?anterior thalamic interconnections are together vital for human episodic memory and rodent event memory. Evidence has emerged for the existence of a series of parallel temporal?diencephalic pathways that function in a reciprocal manner, both directly and indirectly, between the hippocampal formation and the anterior thalamic nuclei. These extended pathways also involve the mammillary bodies, the retrosplenial cortex and parts of the prefrontal cortex. Recent neuropsychological findings reveal the disproportionate importance of these hippocampal?anterior thalamic systems for recollective rather than familiarity-based recognition, while anatomical studies highlight the precise manner in which information streams are kept separate but can also converge at key points within these pathways. These latter findings are developed further by electrophysiological stimulation studies showing how the properties of the direct hippocampal?anterior thalamic projections are often opposed by the indirect hippocampal projections via the mammillary bodies to the thalamus. Just as these hippocampal?anterior thalamic interactions reflect an interdependent system, so it is also the case that pathology in one of the component sites within this system can induce dysfunctional changes to distal sites both directly and indirectly across the system. Such distal effects challenge more traditional views of neuropathology as they reveal how extensive covert pathology might accompany localised overt pathology, and so impair memory.
PUBLISHED
Keywords: Neuroscience; hippocampus; Neuroscience